PENGARUH TOTAL QUALITY MANAGEMENT, SISTEM PENGUKURAN KINERJA, DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL (Studi Kasus pada PT Telkom Surakarta) - Fadjar Harimurti, Octora Tita Audina, Djoko Kristianto & (Universitas Slamet Riyadi, 2018)
This study aims to examine the effect of Total Quality Management, performance measurement system, and reward system of the managerial performance. The object of this study is PT Telkom Surakarta. Sample in this study as much as 72. The technique of collecting data is done by the spread of questionairre. The result of this study use F test show Total Quality Management, performance measurement system, and reward system simultaneously effect to managerial performance. The result t test show Total Quality Management and performance measurement system have no significant positive effect, while reward system has a significant positive effect on managerial performance. The conclusion is Total Quality Management, performance measurement system, and reward system simultaneously effect to managerial performance. Therefore, PT Telkom Surakarta is suggested to maintain Total Quality Management, performance measurement system, and reward system to take decision of managerial performance. Keywords: Total Quality Management, performance measurement system, reward system, and managerial performance